2023
DOI: 10.1149/2162-8777/acbfde
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a PANI/MnO2 Nanocomposite-Based Supercapacitor/Diode Under DC Magnetic Field and Visible and Ultraviolet Photon Irradiation

Abstract: Polyaniline/Manganese dioxide (PANI/MnO2) nanocomposite has been successfully prepared by in situ polymerization method. The X-ray Diffraction (XRD) data confirm the formation of PANI/MnO2 nanocomposites. Fourier Transform Infrared (FT-IR) spectroscopy confirms the vibrationsdominant by metal oxide and polymer in the complex format. The Scanning Electron Microscope (SEM) shows that these nanocomposites exhibits nano rods like morphologies. The optical properties were studied by UV–visible Spectroscopy and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…We carried out a dynamic study called reverse recovery time measurements. 76,77 Here in these studies, a well established difference in control and tumor DNA samples could be observed (see Fig. 9b-9d ).…”
Section: Resultssupporting
confidence: 55%
“…We carried out a dynamic study called reverse recovery time measurements. 76,77 Here in these studies, a well established difference in control and tumor DNA samples could be observed (see Fig. 9b-9d ).…”
Section: Resultssupporting
confidence: 55%
“…Also, dislocation density (γ), defined as a number of dislocation lines in the unit volume in a nanocrystal, was calculated by using the formula below: [35,36] γ=1/()Dhlk2 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr \gamma = 1/{\rm{ }}\left( {D_{{\rm{hlk}}} } \right)^2 \hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
“…Also, dislocation density (γ), defined as a number of dislocation lines in the unit volume in a nanocrystal, was calculated by using the formula below: [35,36]…”
Section: Structural Analysismentioning
confidence: 99%